A Descriptive Qualitative Study on Types of Teachers' Questions in Classroom Interaction - Kakerissa, Wenda Marlin (Huele: Journal of Applied Linguistics, Literature and Culture, 2021)
Teachers' questions have become a vital role in building a well classroom interaction. The aim of this study is to qualitatively describe about teachers' questions in building classroom interaction in teaching and learning process. A qualitative descriptive research design was done by analyzing a video recording and interview with classroom English teacher who was also one of the participants of this study. A framework that was used in this study in analyzing teachers' questions is display and referential questions and the other three types of questions (confirmation checks, comprehension checks, and clarification request) proposed by Long and Sato. The result revealed that the classroom teacher used five types of questions in building classroom interaction in teaching and learning process. Other researchers may conduct the further research on how students respond towards teachers' questions, and also to see a more detail about the influence of questioning strategy in motivating students to speak out fully in English.